Constructing Harmony as the Collective Conscience of the Donggala Community, Central Sulawesi - Surahman (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Tadulako, 2024)
Social and system as a fundamental building blocks of individuals in society become important elements of the cohesion and harmony of citizens. Social construction is contained in the creation of a harmonious order of society, upholding kinship relations inherited from predecessors, then metamorphosing into a collective conscience, a joint agreement of citizens, then processed into the basic values of citizenship. Donggala Regency, part of the Central Sulawesi region, has so far integrated its society based on the rules of tolerance between migrants and local communities, which they pass down from generation to generation to their children and grandchildren. The strong approach of cultural tolerance among all tribes in the area positions Donggala as a harmonious, safe, and peaceful area. Various social upheavals are not visible in social interactions in society. Donggala's cultural heritage from various tribes (migrants and natives) is integrated into social life while binding its people as a system. Such conditions make Donggala harmoniously integrated; its residents dynamize themselves based on cultural heritage and build social relations based on historical traditions supported by strong individual unity, so that they are integrated into a citizenship system wheretolerance becomes their social communication.